2022
DOI: 10.1002/aepp.13259
|View full text |Cite
|
Sign up to set email alerts
|

EU regulation of genetically modified microorganisms in light of new policy developments: Possible implications for EU bioeconomy investments

Abstract: Many developments in the bioeconomy depend on the use of genetically modified microorganisms (GMMs).GMMs are used in bioreactors to convert biomass into food, feed, and energy products. The recent judgment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Policymakers can support development not only by supporting investments via subsidies but also by providing a stimulating policy environment ( Smith et al, 2021 ). Cultivating transgenic tobacco plants and extracting and processing the CGP in Argentina appears to be a more cost-efficient strategy than that in which the tobacco is cultivated in Europe or Argentina and the crude CGP is exported to the EU, as indicated by recent research on the costs for approvals ( Wesseler, et al, 2022 in press).…”
Section: Discussionmentioning
confidence: 99%
“…Policymakers can support development not only by supporting investments via subsidies but also by providing a stimulating policy environment ( Smith et al, 2021 ). Cultivating transgenic tobacco plants and extracting and processing the CGP in Argentina appears to be a more cost-efficient strategy than that in which the tobacco is cultivated in Europe or Argentina and the crude CGP is exported to the EU, as indicated by recent research on the costs for approvals ( Wesseler, et al, 2022 in press).…”
Section: Discussionmentioning
confidence: 99%
“…They often include costs for receiving approval for introducing new prod-ucts. These approval costs can be considered irreversible (Wesseler et al, 2022). They include not only the direct costs for generating the information approval but also the time length of the approval process.…”
Section: Importance Of Uncertainty and Irreversibility For Innovation...mentioning
confidence: 99%
“…Approval policies can also differ by jurisdiction and either increase or decrease the size of the market. Studies have shown that the irreversibility effect of approval polices can be substantial (Wesseler et al, 2022). Approval must not only be seen as a cost.…”
Section: Importance Of Uncertainty and Irreversibility For Innovation...mentioning
confidence: 99%
“…The first genetic modified (preventing from turning brown) mushroom A. bisporus received regulatory declaration by the US Department of Agriculture (USDA) since 2016 (Waltz, 2016 ; Wesseler et al, 2022 ), which implied the great potential of gene‐edited mushroom application in global food or nutritive fortifier markets. The CRISPR/Cas9 genome editing technology has also been applied to other mushroom, containing Pleurotus ostreatus (Boontawon, Nakazawa, Horii, et al, 2021 ; Boontawon, Nakazawa, Inoue, et al, 2021 ; Boontawon, Takehito, Xu, et al, 2021 ), P. eryngii (Wang et al, 2021 ), Ganoderma lucidum (Liu et al, 2020 ; Qin et al, 2017 ; Tu et al, 2021 ; Wang et al, 2020 ), Schizophyllum commune (Jan Vonk et al, 2019 ), Coprinopsis cinerea (Sugano et al, 2017 ), Lentinula edodes (Moon et al, 2021 ) and C. militaris (Chen et al, 2018 ; Zou, Xiao, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%